DALL’EPISTOLARIO DI CARLO ERMES VISCONTI, NOTE SU VICENDE DI MONUMENTI MILANESI (Istituto Lombardo - Accademia di Scienze e Lettere - Rendiconti di Scienze, 2014)
The unpublished letters of Carlo Ermes Visconti (1834-1911) goad a further investigation on the architectural events discussed in Milan during the last decades of the nineteen century, especially, referring to the Lazzaretto and the restoration of the Sforza Castle. The correspondence of the marquis Visconti, with Luca Beltrami, Gaetano Negri and Giovanni Celoria, at least, shows the nature of his relationship with the cultural and political milieu he attended supporting a deeper analysis of his profile, not only the biographic one. Contents and correlations singled out throught this documents among figures, actions and circumstances allow a few remarks and some new perspectives about his opinion on restoration and preservation of the ancient buildings and, furthermore, the role he played in the settlement of civic collections and museums, being these topics different part of a same goal.